2022
DOI: 10.3389/fmolb.2022.826505
|View full text |Cite
|
Sign up to set email alerts
|

Combining Coarse-Grained Simulations and Single Molecule Analysis Reveals a Three-State Folding Model of the Guanidine-II Riboswitch

Abstract: Riboswitch RNAs regulate gene expression by conformational changes induced by environmental conditions and specific ligand binding. The guanidine-II riboswitch is proposed to bind the small molecule guanidinium and to subsequently form a kissing loop interaction between the P1 and P2 hairpins. While an interaction was shown for isolated hairpins in crystallization and electron paramagnetic resonance experiments, an intrastrand kissing loop formation has not been demonstrated. Here, we report the first evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In particular, all base-stacking interactions between consecutive nucleotides and hydrogen-bond interactions between any bases G and C, A and U, or G and U are included ( 48 ). Therefore, the model captures non-native secondary structure interactions as shown in previous work ( 54 , 73 ) and for TERRA25 (see Supplementary Figure S3). Moreover, it has been shown that TIS reproduces experimental thermodynamic and structural data for several different RNA molecules including ribozyme formation or riboswitch folding under a variety of solvent conditions ( 52 , 54 , 73 ).…”
Section: Materials and Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…In particular, all base-stacking interactions between consecutive nucleotides and hydrogen-bond interactions between any bases G and C, A and U, or G and U are included ( 48 ). Therefore, the model captures non-native secondary structure interactions as shown in previous work ( 54 , 73 ) and for TERRA25 (see Supplementary Figure S3). Moreover, it has been shown that TIS reproduces experimental thermodynamic and structural data for several different RNA molecules including ribozyme formation or riboswitch folding under a variety of solvent conditions ( 52 , 54 , 73 ).…”
Section: Materials and Methodsmentioning
confidence: 90%
“…TIS, the three-interaction site model developed by Thirumalai and coworkers, is a simple low-resolution model. Its efficiency and accuracy to describe folding has been demonstrated for a variety of RNA molecules ranging in size from larger molecules such as ribozyme ( 52 ) to smaller RNAs like riboswitch ( 54 ), pseudoknot ( 50 ), and hairpin ( 49 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the model captures non-native secondary structure interactions as shown in previous work (54,73) and for TERRA25 (see Figure S3). Moreover, it has been shown that TIS reproduces experimental thermodynamic and structural data for several different RNA molecules including ribozyme formation or riboswitch folding under a variety of solvent conditions (52,54,73). With these prerequisites, TIS is ideal to resolve intermediates states and their frequency of occurrence in the folding of rG4 systems.…”
Section: Intermediate States In Tismentioning
confidence: 87%
“…In particular, all basestacking interactions between consecutive nucleotides and hydrogen-bond interactions between any bases G and C, A and U, or G and U are included (48). Therefore, the model captures non-native secondary structure interactions as shown in previous work (54,73) and for TERRA25 (see Figure S3). Moreover, it has been shown that TIS reproduces experimental thermodynamic and structural data for several different RNA molecules including ribozyme formation or riboswitch folding under a variety of solvent conditions (52,54,73).…”
Section: Intermediate States In Tismentioning
confidence: 99%
“…understood despite studies probing the selectivity 54,57 of the AD to Gdm + . While no theoretical studies on the ligand binding mechanism of ykkC-I exist to date, a coarse-grained study based on the coarse-grained three-interaction site (TIS) shows that the guanidine-AD of the mini-ykkC guanidine-II aptamer exhibits a three-state model composed of (i) an open conformation, (ii) the kissing-loop conformation, and (iii) a novel Mg 2+ -dependent state 73 in the absence of guanidine. Another study, using extensive molecular dynamics (MD) simulations, showed the role of the binding pocket in discriminating between Gdm + and its close relative, urea.…”
Section: Introductionmentioning
confidence: 99%